Pick a Horse, Ditch the Goat: the Rise of the Spoiler Frame in a Bipartisan Election Discourse - (:unkn) unknown (My University, 2021)
Increasingly, public opinion shows Republican and Democratic presidential candidates are some of the most onerous in recorded history, and Americans want to see third-party options alongside them. Half of Americans use televised news to stay informed, but the two-party horserace leaves little room for the multiple candidates on the ballot. This analysis explores the prominent horserace discourse of the 2012 and 2016 televised coverage of the U.S. presidential races and the “spoiler effect” frame within. Following Jill Stein’s Green Party candidacy through the months surrounding each election, the coverage advanced her portrayal from “nonfactor” to “spoiler” despite the consistency in her campaign platform. During both elections, journalists delegitimized Stein and other third-party candidates with subframes the author calls “undeserved,” “the scarlet Nader,” and the “laughingstock.” These frames are evidence of the intensely partisan two-party political system and corresponding media; their use narrows the election discourse.
Keywords: 2012 presidential election; 2016 presidential election; framing; horse race; Jill Stein; spoiler effect